2019
DOI: 10.21608/edj.2019.76027
|View full text |Cite
|
Sign up to set email alerts
|

Digital PEEK framework and patient satisfaction compared to conventional metal framework in removable partial dentures. A clinical trial

Abstract: Introduction: Utilization of removable partial dentures (RPD) is inevitable in some patients that are not indicated for any other treatment option, thus patient satisfaction with this line of treatment is of great importance. However, a notable need exists to advance materials and fabrication technologies due to the undesirable health outcomes linked with current RPDs. Aim: In this study patient satisfaction with conventionally manufactured metal RPD framework, was compared with their satisfaction using digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The aim of this study was to evaluate the effect of PEEK and Co-Cr as framework material for extra coronal attachment retained RDP on bone height changes to distal abutments and patient satisfaction, as (Mohamed, and Rasha, 2019) 32 concluded that Digitally fabricated RDP frameworks made of PEEK material allows RDPs patients to be more satisfied with their prosthesis than conventional metallic frameworks, thus extending the application of RDP and decreasing patients' rejection to the removable appliances, which will serve to restore more partially edentulous cases with great satisfaction and least complaints.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to evaluate the effect of PEEK and Co-Cr as framework material for extra coronal attachment retained RDP on bone height changes to distal abutments and patient satisfaction, as (Mohamed, and Rasha, 2019) 32 concluded that Digitally fabricated RDP frameworks made of PEEK material allows RDPs patients to be more satisfied with their prosthesis than conventional metallic frameworks, thus extending the application of RDP and decreasing patients' rejection to the removable appliances, which will serve to restore more partially edentulous cases with great satisfaction and least complaints.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of the denture base has a direct effect on the size of the oral cavity specially in the vertical direction as it becomes shorter so the presence of more vertical space in the Co-Cr group making more freedom and comfort for the tongue articulating position nearest to the pre-prosthesis position with the palatal tissue. (23) Regarding patient satisfaction with each prosthesis; patient comfort was higher in the PEEK group than Co-Cr group and this could be attributed to the weight of the prosthesis which usually has a major influence on the patient's comfort. (24,25) PEEK has a low specific weight thus allowing the construction of light weighed prostheses with good functionality offering high patient satisfaction and comfort through function.…”
Section: Fig (2) Bar Chart Showing the Results Of Vas Scores For Both...mentioning
confidence: 91%
“…This is in agreement with who stated that PEEK frameworks allowed the patients to be more satisfied with their removable prosthesis more than conventional Co-Cr RPD, which will help to rehabilitate more partially edentulous patients with high appreciation and minimum complaints. (28,29) Also, this suggests that the appearance of patients with missing anterior teeth plays a more influential role in their satisfaction with their prosthesis than their ability to speak (speech quality) with their prosthesis.…”
Section: Fig (2) Bar Chart Showing the Results Of Vas Scores For Both...mentioning
confidence: 99%
“…Various clinical reports [ 18 , 71 , 78 ] have shown that PEEK (Bio-HPP) RPDs have a lower specific weight than CoCr RPDs, providing high patient satisfaction and comfort [ 18 ]. A randomized controlled trial [ 83 ] compared the satisfaction of 10 patients asked to wear metal and PEEK framework RPDs for 3 months. Patients were more satisfied with the milled PEEK framework RPDs than with the CoCr framework RPDs.…”
Section: Clinical Performance For Removable Peek Prosthodonticsmentioning
confidence: 99%